The Use of Ambon Banana Starch (Musa paradisiaca var. sapientum L.) as a New Binder in Tablet Formulation : Penggunaan Pati Pisang Ambon (Musa paradisiaca var. sapientum L.) Sebagai Bahan Pengikat Baru Dalam Formulasi Tablet - Ikhwatun Mutmainnah; Santi Sinala; Sisilia TR Dewi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Synthetic materials are commonly used as binders in tablet formulations, this causes the price of tablets to be more expensive. For this reason, new discoveries are sought that can replace synthetic materials by utilizing materials from nature. One of the binders that comes from natural ingredients and is easily obtained is the Ambon Banana Starch (Musa paradisiaca var. sapientum (L.)). Objectives: This study was conducted to determine the physical characteristics of paracetamol tablets from Ambon banana starch (Musa paradisiaca var. sapientum L.) as a binder. Materials and Methods: Paracetamol tablets were compressed using the wet granulation method by adding a binder in the form of Ambon banana starch mucilago. The consentration of Ambon banana starch used was Formula I (15%), Formula II (17.5%) and Formula III (20%). Evaluation of the physical characteristics of the preparation is determined through the parameters of granule testing and tablet testing. Results: Formulation I, II, and III have met the requirements for the granule test. Meanwhile, in tablet testing, the results of size uniformity test, weight uniformity test, hardness test, and disintegration time test met the requirements for all formulations. However, in the friability test, Formula I (15%) did not meet the requirements with a value of 2.07% (requirement <1%), while formulas II and III had met the requirements. Conclusions: This study showed that Ambon banana starch can be used as a binder in tablet formulation.